Claudin18.2-Specific Chimeric Antigen Receptor Engineered T Cells for the Treatment of Gastric Cancer - Jiang, Hua; Shi, Zhimin; Wang, Peng; Wang, Cong; Yang, Linlin; Du, Guoxiu; Zhang, Honghong; Shi, Bizhi; Jia, Jie; Li, Qixiang; Wang, Huamao; Li, Zonghai (JNCI : Journal of the National Cancer Institute, 2019)
Claudin18.2 (CLDN18.2), a gastric-specific membrane protein, has been regarded as a potential therapeutic target for gastric cancer and other cancer types. The aim of our study was to elucidate whether chimeric antigen receptor T (CAR T) cells redirected to CLDN18.2 have the potential to be used in the treatment of this deadly disease. CLDN18.2-specific humanized antibodies were developed using hybridoma and humanization technology. CLDN18.2-specific CAR T cells were prepared by lentiviral vector transduction. In vitro antitumor activities and cytokine production of the CAR T cells to gastric cancer cell lines were examined by cytotoxicity and ELISA assay. In vivo antitumor activities of CAR T cells were evaluated in mice bearing gastric cancer cell line and patient-derived tumor xenograft (PDX) models (n ≥ 6 mice per group). All statistical tests were two-sided. Humanized CLDN18.2-specific hu8E5 and hu8E5-2I single-chain fragment variables (scFv) were successfully developed. CLDN18.2-specific CAR T cells were developed using hu8E5 or hu8E5-2I scFv as targeting moieties. Both hu8E5-28Z and hu8E5-2I-28Z CAR T cells comprising the CD28 costimulatory domain potently suppressed tumor growth in a cancer cell line xenograft mouse model (mean [SD] tumor volume: hu8E5-28Z = 118.0 [108.6] mm3 and hu8E5-2I-28Z group = 75.5 [118.7] mm3 vs untransduced T cell group = 731.8 [206.3] mm3 at day 29 after tumor inoculation, P < .001). Partial or complete tumor elimination was observed in CLDN18.2-positive gastric cancer PDX models treated with the hu8E5-2I-28Z CAR T cells (P < .001), which persist well in vivo and infiltrate efficiently into the tumor tissues. Although the CLDN18.2 CAR T cells could lyse target cells expressing murine CLDN18.2 (mCLDN18.2), no obvious deleterious effect on the normal organs including the gastric tissues was observed in the mice. CLDN18.2-specific CAR T cells could be a promising treatment strategy for gastric cancer and potentially other CLDN18.2-positive tumors.